2016
DOI: 10.1038/bmt.2016.81
|View full text |Cite
|
Sign up to set email alerts
|

How do I manage hyperglycemia/post-transplant diabetes mellitus after allogeneic HSCT

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients frequently develop glucose intolerance and post-transplant diabetes mellitus (PTDM). The clinical importance of PTDM and its detrimental impact on HSCT outcomes are underrecognized. After allo-HSCT, various mechanisms can contribute to the development of PTDM. Here we review information about hyperglycemia and PTDM after allo-HSCT as well as PTDM after solid organ transplantation and describe ways to manage hyperglycemia/PTDM after allog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 113 publications
1
23
0
Order By: Relevance
“…55 Dysregulated glucose homeostasis may persist beyond this first phase or emerge during long-term follow-up in the form of 3 related entities: 1) Type 2 Diabetes Mellitus (T2DM), encompassing conditions characterized by hyperglycemia due to various degrees of impairment of insulin secretion or action; 56 2) pre-diabetic states (PDS) where fasting or post-prandial glucose levels are chronically above the normal range without reaching those diagnostic of DM; 57, 58 and 3) Insulin resistance (IR), a metabolic trait that predisposes to PDS and type 2 DM, the most prevalent form of DM in the general adult population. 56 …”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…55 Dysregulated glucose homeostasis may persist beyond this first phase or emerge during long-term follow-up in the form of 3 related entities: 1) Type 2 Diabetes Mellitus (T2DM), encompassing conditions characterized by hyperglycemia due to various degrees of impairment of insulin secretion or action; 56 2) pre-diabetic states (PDS) where fasting or post-prandial glucose levels are chronically above the normal range without reaching those diagnostic of DM; 57, 58 and 3) Insulin resistance (IR), a metabolic trait that predisposes to PDS and type 2 DM, the most prevalent form of DM in the general adult population. 56 …”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Emerging studies have shown that among people with cancer, those who have received hematopoietic cell transplant, are at higher risk for diabetes following treatment (Clark, Savani, Mohty, & Savani, 2016; Fuji et al, 2016). Therefore, it is imperative that hyperglycemia be accurately measured in order to be well managed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients often have hyperglycemia after allogeneic HSCT, as reviewed recently. 5,59 Considering the importance of neutrophil function in the control of bacterial infections, we can assume that better glucose control might reduce the risks of both bacterial and fungal infections. In particular, glucose control after allogeneic HSCT during the early neutropenic period could be crucial, as the risk of bacterial and fungal infections is high due to profound neutropenia, and the risk of developing hyperglycemia is also high due to various causes such as inflammation associated with conditioning regimens and total parenteral nutrition.…”
Section: Possible Implications Of Glucose Control To Reduce the Risk mentioning
confidence: 99%
“…Several treatment procedures, such as solid organ transplantation and hematopoietic stem cell transplantation (HSCT), are intrinsically associated with a high risk of mold infections and also correlated with an increased risk of post-transplant DM. 5 The mechanism whereby the presence of DM affects the incidence of mold infections in such cases is intriguing. Here, we aim to summarize the information about the increased risk of mold infections in patients with DM, and propose possible interventions to reduce this risk.…”
Section: Introductionmentioning
confidence: 99%